DOA Estimation Method for Wideband Signal using Nested Antenna Array Based on Matrix Pencil Algorithm - Han, Trong Thanh (Old Journal, 2019)
Radio Direction Finding (RDF) systems have a lot of applications in both civil and military area such as Radio Navigation, Electronic warfare or Emergency Aid and intelligent operations. In modern communication system, wideband signals are widely used especially in wireless localization field. In this paper, a novel RDF system using Nested Antenna Array and Total Forward Backward Matrix Pencil Algorithm is proposed. This system can calculate the DOA of signals coming from the number of sources more than the number of antenna elements. The simulation results for DOA estimation of wideband signals using the proposed system will be shown and analyzed to verify its performance.